2015
DOI: 10.1007/s13577-015-0117-3
|View full text |Cite
|
Sign up to set email alerts
|

Slug contributes to gemcitabine resistance through epithelial-mesenchymal transition in CD133+ pancreatic cancer cells

Abstract: CD133-positive pancreatic cancer is correlated with unfavorable survival despite current development of therapy. Slug acts as a master regulator of epithelial-mesenchymal transition (EMT) which is the essential process in cancer progression. The aim of this study was to investigate the role of Slug in gemcitabine treatment for CD133-positive pancreatic cancer cells. We used a previously established pancreatic cancer cell line expressing high level of CD133 (Capan-1M9), which also expresses high level of Slug. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
23
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 36 publications
(25 citation statements)
references
References 37 publications
2
23
0
Order By: Relevance
“…We have demonstrated the critical roles played by slug in drug resistance in the metastatic ovarian cancer subpopulation. This finding was consistent with several previous reports that slug conferred resistance to anti-cancer drugs 12. , 14.…”
Section: Resultssupporting
confidence: 94%
“…We have demonstrated the critical roles played by slug in drug resistance in the metastatic ovarian cancer subpopulation. This finding was consistent with several previous reports that slug conferred resistance to anti-cancer drugs 12. , 14.…”
Section: Resultssupporting
confidence: 94%
“…These findings identify a new function for NatD in gene expression regulation, and extend our understanding of epigenetic regulation of EMT via Nt-acetylation of histone H4. Slug, a key regulator of EMT, has been identified as one of the major drivers of chemoresistance, and is associated with cancer stem cell properties 36 , 37 . In our results, we found that Slug is a direct epigenetic target of NatD to mediate EMT processes of lung cancer cells.…”
Section: Discussionmentioning
confidence: 99%
“…The presence of platelets around breast cancer primary tumour cells was associated with EMT morphological features and chemotherapy resistance [ 106 ]. Independent of platelet activity, EMT has been shown to impart chemotherapy resistance in lung [ 107 ], pancreatic [ 108 ], breast [ 109 ] and ovarian cancers [ 110 ]. Zheng et al, demonstrated using a pancreatic adenocarcinoma mouse model with deleted mesenchymal transcriptional factors, Snail and Twist, that EMT inhibition did not prevent metastasis but contributed significantly to enhanced gemcitabine sensitivity [ 111 ].…”
Section: The Role Of Platelets In Chemotherapy Resistancementioning
confidence: 99%